Primary and tertiary health professionals' views on the health-care of patients with co-morbid diabetes and chronic kidney disease – a qualitative study. Issue 1 (December 2016) - Lo, Clement; Ilic, Dragan; Teede, Helena; Fulcher, Greg; Gallagher, Martin; Kerr, Peter; Murphy, Kerry; Polkinghorne, Kevan; Russell, Grant; Usherwood, Timothy; Walker, Rowan; Zoungas, Sophia
Abstract Background Health-care for co-morbid diabetes and chronic kidney disease (CKD) is often sub-optimal. To improve health-care, we explored the perspectives of general practitioners (GPs) and tertiary health-care professionals concerning key factors influencing health-care of diabetes and CKD. Methods A total of 65 health professionals were purposively sampled from Australia's 2 largest cities to participate in focus groups and semi-structured interviews. Four focus groups were conducted with GPs who referred to 4 tertiary health services in Australia's 2 largest cities, with 6 focus groups conducted with tertiary health-care professionals from the 4 tertiary health services. An additional 8 semi-structured interviews were performed with specialist physicians who were heads of diabetes and renal units. All discussions were facilitated by the same researcher, with discussions digitally recorded and transcribed verbatim. All qualitative data was thematically analysed independently by 2 researchers. Results Both GPs and tertiary health-care professionals emphasised the importance of primary care and that optimal health-care was an inter-play between patient self-management and primary health-care, with specialist tertiary health-care support. Patient self-management, access to specialty care, coordination of care and a preventive approach were identified as key factors that influence healthcare and require improvement. Both groups suggested that an integrated specialist diabetes-kidney service could improve care. Unit heads emphasised the importance of quality improvement activities. Conclusions GPs and tertiary health-care professionals emphasised the importance of patient self-management and primary care involvement in the health-care of diabetes and CKD. Supporting GPs with an accessible, multidisciplinary diabetes-renal health service underpinned by strong communication pathways, a preventive approach and quality improvement activities, may improve health-care and patient outcomes in co-morbid diabetes and CKD.